Ideologi Gender Dalam Film Soviet ДВЕНАДЦАТЬ МЕСЯЦЕВ ‘Dua Belas Bulan’ - Widyastuti Thera; Annisa Salshabia Nur Utami (SASDAYA: Gadjah Mada Journal of Humanities, 2021)
Fairy tales are often identified with messages to be conveyed to readers, and can also contain certain ideologies. Many studies have analyzed the relations between fairy tales and gender ideology. Therefore, the writer chose the Soviet film entitled Двенадцать месяцев 'Twelve Months' (1972) as the source of research data, because there are additional elements written by Marshak. The purpose of this research is to describe the actant scheme and the characterization in the film, and to analyze whether gender ideology is present in the film, and how the ideology is presented. The approach used is the Greimas' actantial model approach. The method used in this research is qualitative and descriptive analytical methods. The result of this research shows that there are still gender stereotypes in the film, which can be seen from the actantial schemes and the characterization of the characters.